2012 - (2^2011+2^2010+2^2009+...+2^+2^1+2^0) tính
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Kết quả : 0
Giải:
(-2012+2012)+(-2011+2011)+(-2010+2010)+(-2009+2009)+................+(-3+3)+(-2+2)+(-1+1)+0=0
Ta có \(B=\left(\frac{2010}{2}+1\right)+\left(\frac{2009}{3}+1\right)+...+\left(\frac{2}{2010}+1\right)+\left(\frac{1}{2011}+1\right)+1\)
\(B=\frac{2012}{2}+\frac{2012}{3}+...+\frac{2012}{2010}+\frac{2012}{2011}+\frac{2012}{2012}\)
\(B=2012.\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2010}+\frac{1}{2011}+\frac{1}{2012}\right)\)
B=2012.A
=>A/B=1/2012
Ta có: \(\frac{1}{2^2}+\frac{1}{3^2}+...+\frac{1}{2010^2}<\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{2009.2010}\)
\(<1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{2009}-\frac{1}{2010}\)
\(<1-\frac{1}{2010}\)
\(<\frac{2009}{2010}<1\)
=>N<1
Đề: Tính???
20122 - 20112 + 20102 - 20092 + ... + 22 - 12
= (2012 + 2011) (2012 - 2011) + (2010 + 2009) (2010 - 2009) + ... + (2 + 1) (2 - 1)
= 2012 + 2011 + 2010 + 2009 + ... + 2 + 1
Số số hạng là: (2012 - 1) : 1 + 1 = 2012 (số)
Tổng bằng: (1 + 2012) . 2012 : 2 = 2025078
Vậy 20122 - 20112 + 20102 - 20092 + ... + 22 - 12 = 2025078.
Ta có: x=2011 \(\Rightarrow\)x+1=2012
\(\Rightarrow A=x^{2011}-\left(x+1\right).x^{2010}\)\(+\left(x+1\right)x^{2009}\)\(-\left(x+1\right)x^{2008}+...\)\(-\left(x+1\right)x^2+\left(x+1\right)x-1\)
=\(x^{2011}\)\(-x^{2011}-x^{2010}+x^{2010}+x^{2009}-x^{2009}-\)...\(-x^2+x^2+x-1\)
= \(x-1=2011-1=2010\)
=
S = 2012-2011+2010-2009+......+2-1
S= (2012-2011)+(2010-2009)+.........+(2-1) [có 1006 cặp)
S= 1+1+..........+1 [có 1006 số 1]
Vậy S= 1.1006 = 1006
`2012 - ( 2^2011+ 2^2010 + 2^2009 + ... + 2^2 + 2^1 + 2^0 )`
Đặt `A = 2012 - ( 2^2011+ 2^2010 + 2^2009 + ... + 2^2 +2^1 + 2^0 )`
Đặt `B = 2^2011+ 2^2010 + 2^2009 + ... + 2^2 + 2^1 + 2^0`
`2B = 2( 2^2011+ 2^2010 + 2^2009 + ... + 2^2 + 2^1 + 2^0 )`
`2B = 2^2012+ 2^2011 + 2^2010 + ... + 2^3 +2^2 + 2^1`
`2B - B = ( 2^2012+ 2^2011 + 2^2010 + ... + 2^3 +2^2 + 2^1 ) - ( 2^2011+ 2^2010 + 2^2009 + ... + 2^2 +2^1 + 2^0 )`
`B = 2^2012+ 2^2011 + 2^2010 + ... + 2^3 +2^2 + 2^1 - 2^2011- 2^2010 - 2^2009 - ... - 2^2 - 2^1 - 2^0`
`B = ( 2^2012 - 2^0 ) + ( 2^2011 - 2^2011 ) + ... +( 2^2 - 2^2 ) + ( 2^1 - 2^1 ) `
`B = 2^2012 - 1`
Thay B và A ta được:
`A = 2012 - ( 2^2012 - 1 )`
A = 2012 - 2^2012 + 1
HT nhen